1,3-propanodiol: produção, aplicações e potencial biotecnológico - Silva, Gervásio Paulo Da; Contiero, Jonas [UNESP]; Ávila Neto, Paulo Marcelo [UNESP]; Lima, Cristian Jacques Bolner De [UNESP] (Sociedade Brasileira de Química, 2014)
1,3-propanediol is a high-value specialty chemical which has many industrial applications. Its main use is the production of the polymer polypropylene terephthalate, a thermoplastic used in the textile and automobile industries. The interest in 1,3-propanediol production from glycerol bio-conversion has increased after the employment of biodiesel by various countries, being produced by chemical synthesis from petroleum intermediates or biotechnologically by microbial fermentation. Glycerol is an abundant low-cost byproduct from biodiesel refineries, and it is the only substrate that can be naturally or enzymatically converted to 1,3-propanediol by microbial fermentation. In this review, information on 1,3-propanediol's importance, production and purification are presented, along with results from recent research on glycerol microbial conversion to 1,3-propanediol. The bio-production of this intermediate compound from glycerol is very attractive both economically and environmentally, since it allows the replacement of fossil fuels by renewable resources.
1,3-propanediol: production, applications and biotechnological potential
Keywords: Green Chemistry; glycerol fermentation; 1,3-propanediol